A multilayer iron-cobalt-nickel composite permanent magnetic film and a method for manufacturing the same
By using magnetic control sputtering and ALD technology during the preparation of multi -layer magnetic thin film, the FECONI alloy layer is seized step by step, and external magnetic fields are applied during the deposition and annealing process. The problem realizes the excellent magnetism and structural stability of the film.
Patent Information
- Application Number
- CN202411554977.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the preparation process of multi-layer magnetic films, the problems of insufficient interlayer bonding force, uneven grain size, difficulty in controlling magnetic properties, and large hysteresis losses.
The magnetic sputtering technology and the atomic layer deposition (ALD) technology are adopted, and FE, CO, Ni, and rare earth element atomic layers are used step by step to form a FECONI alloy layer with composite rare earth elements. Optimize magnetic orientation and structural stability.
It achieves excellent magnetic properties and structural stability of the film, improves magnetic anisotropy, coercivity, saturation magnetization and remanence, and is suitable for high-frequency magnetic applications.
Smart Images

Figure CN119049881B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnetic films, and in particular to a multilayer iron-cobalt-nickel composite permanent magnetic film and a manufacturing method thereof. Background Art
[0002] In recent years, with the rapid development of information technology and electronic devices, high-performance permanent magnetic materials are increasingly used in modern industry, especially in the fields of microelectronics and nanotechnology. As an important magnetic material, FeCoNi alloy has attracted much attention due to its excellent magnetic properties and thermal stability. FeCoNi alloy is widely used in high-frequency magnetic components, magnetic recording materials and sensors due to its high saturation magnetization, high coercive force and excellent magnetic anisotropy. Although traditional magnetic film preparation methods, such as physical vapor deposition (PVD) and chemical vapor deposition (CVD), can produce high-quality FeCoNi magnetic films, they still have certain limitations in terms of interlayer bonding force, film uniformity and magnetic property control. For example, the Chinese patent (CN103205787B) discloses a method for preparing a metal permanent magnetic film with a multilayer film structure, which relates to the production technology field of metal permanent magnetic films with a multilayer film structure for magnetic recording, information storage and reproduction of information recording. The invention uses a platinum electrode as a counter electrode, a polished copper sheet or brass sheet as a working electrode, and a saturated calomel electrode as a reference electrode to sequentially deposit an Sm metal layer and a Co metal layer on the surface of the copper sheet or brass sheet in an electrolyte. The invention requires simple equipment, and the production process is easy to operate, which can greatly improve production efficiency and is suitable for industrial mass production; by controlling the deposition time, the thickness of the Sm film layer can be controlled and adjusted, thereby increasing the Sm content in the film, which is conducive to obtaining better magnetic properties.
[0003] In addition, with the development demand of multilayer composite magnetic materials, how to improve the interlayer bonding force while optimizing the magnetic properties of each layer and realizing the multifunctionality of magnetic materials has become a hot topic of current research. However, the existing technology has many shortcomings in the preparation process of multilayer magnetic films. First, due to the lattice mismatch and thermal expansion coefficient differences between different materials, the interlayer bonding force is insufficient, and interface defects and film peeling problems are prone to occur. Secondly, it is difficult for traditional deposition methods to achieve precise atomic-level control of each layer of materials, resulting in uneven grain size of the film, affecting the magnetic anisotropy and overall magnetic properties of the film. In addition, the existing technology has limited means of controlling the magnetic properties of the film, and it is difficult to effectively control the magnetic domain structure during the deposition process, resulting in increased hysteresis loss of the film, affecting its performance in high-frequency applications. Summary of the invention
[0004] The existing technology has many shortcomings in the preparation process of multilayer magnetic films. First, due to the lattice mismatch and thermal expansion coefficient differences between different materials, the interlayer bonding force is insufficient, and interface defects and film peeling problems are prone to occur. Secondly, traditional deposition methods are difficult to achieve atomic-level precise control of each layer of material, resulting in uneven grain size of the film, affecting the magnetic anisotropy and overall magnetic properties of the film. In addition, the existing technology has limited means of controlling the magnetic properties of the film, and it is difficult to effectively control the magnetic domain structure during the deposition process, resulting in increased hysteresis losses in the film, affecting its performance in high-frequency applications.
[0005] The present application provides a method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film, comprising the following technical steps:
[0006] Select the substrate material;
[0007] A Ni layer is deposited on the substrate material using magnetron sputtering technology; Fe, Co, Ni and rare earth element atomic layers are deposited on the Ni layer step by step using ALD technology to form a FeCoNi alloy layer of composite rare earth elements; finally, a Ni layer is deposited on the FeCoNi alloy layer using magnetron sputtering technology;
[0008] The deposited film is annealed in an Ar2 atmosphere at a temperature between 400°C and 500°C for 1 to 2 hours;
[0009] During the deposition and annealing of the FeCoNi alloy layer, an external magnetic field is applied with a strength controlled between 100 mT and 300 mT.
[0010] It should be noted that the preparation method of this multi-layer iron-cobalt-nickel composite permanent magnetic film achieves excellent magnetic properties and structural stability of the film through multi-step deposition and annealing treatment. First, a Ni layer is deposited on the substrate material using magnetron sputtering technology. The Ni layer not only provides good adhesion for the subsequently deposited materials, but also lays the foundation for the overall magnetic properties of the film through its soft magnetic properties. The uniform deposition of the Ni layer ensures the stability of the film on the substrate and provides a smooth interface for the subsequent atomic layer deposition (ALD) process.
[0011] Fe, Co, Ni and rare earth element atomic layers are deposited step by step on the Ni layer by ALD technology to form a FeCoNi alloy layer of composite rare earth elements. The self-limiting reaction mechanism of ALD technology ensures the precise control of the thickness and composition of the deposited layer of each element. In particular, the introduction of rare earth elements greatly improves the magnetic anisotropy, coercive force, saturation magnetization and remanence of the alloy layer. The deposition of rare earth elements optimizes the distribution and orientation of magnetic domains by changing the structure of the magnetic phase, which significantly improves the magnetic properties of the film.
[0012] Next, a Ni layer is deposited on the FeCoNi alloy layer using magnetron sputtering technology. This Ni layer not only further protects the FeCoNi alloy layer to prevent it from oxidation in subsequent processing, but also enhances the magnetic field response capability of the overall film through its soft magnetic properties. The introduction of the Ni layer can also improve the surface quality of the FeCoNi alloy layer, reduce surface defects, and play a role in buffering stress in the entire film structure.
[0013] Finally, the deposited film was annealed in an Ar2 atmosphere at a temperature between 400°C and 500°C for 1 to 2 hours. An external magnetic field was applied during both the deposition and annealing processes, and this process had a significant effect on the microstructure and magnetic properties of the film. First, the application of an external magnetic field during the deposition process can guide the magnetic orientation of magnetic elements (such as Fe, Co, Ni and rare earth elements). This magnetic field guidance effect makes these magnetic atoms tend to align along the magnetic field direction in the early stages of film formation, thereby establishing a consistent magnetic domain structure in the film. This consistent magnetic domain arrangement reduces the disordered distribution of the magnetic domain wall, effectively reduces the hysteresis loss, and makes the film exhibit higher magnetic anisotropy and more uniform magnetic behavior. For high-precision magnetic devices, this early magnetic orientation control is particularly critical because it lays the foundation for the overall magnetic properties of the film. The application of an external magnetic field during the annealing process further strengthens this magnetic orientation. The annealing process promotes the diffusion of atoms and the reorganization of grains in the film through high-temperature heat treatment, thereby optimizing the microstructure. When an external magnetic field is present during this process, the magnetic atoms have higher kinetic energy at high temperatures and can be rearranged more effectively in the direction of the magnetic field. This rearrangement not only enhances the consistency of the magnetic domains, but also promotes the preferred orientation growth of the grains, so that the film forms a structure with a highly consistent magnetic orientation after annealing. In addition, the external magnetic field can also help repair the magnetic domain structure defects that may be generated during the deposition stage during the annealing process, thereby further improving the overall magnetic properties of the film, including higher saturation magnetization and coercivity.
[0014] As a preferred technical solution for the preparation of a multilayer iron-cobalt-nickel composite permanent magnetic film, the ALD technology is used to deposit Fe, Co, Ni and rare earth element atomic layers step by step on the Ni layer to form a FeCoNi alloy layer of composite rare earth elements. The specific technical steps include:
[0015] The Fe precursor is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Fe precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Fe precursor to form a metal Fe layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts.
[0016] The Co precursor is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Co precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Co precursor to form a metal Co layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts.
[0017] The Ni precursor is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Ni precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Ni precursor to form a metal Ni layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts.
[0018] The rare earth element precursor is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted rare earth element precursor molecules and by-products. A co-reactant is introduced into the reaction chamber to react with the adsorbed rare earth element precursor to form a rare earth layer. An inert gas is introduced again to remove unreacted co-reactants and by-products.
[0019] The above steps are repeated to gradually form a multilayer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers.
[0020] It should be noted that in the process of atomic layer deposition (ALD) technology, Fe, Co, Ni and rare earth elements are deposited step by step to gradually build up the FeCoNi alloy layer of composite rare earth elements. The mechanism of each deposition step is based on the self-limiting reaction characteristics of ALD. In this process, the precursor molecules are introduced into the reaction chamber through the gas phase, and under the condition of temperature control (150°C to 250°C), the precursors are chemically adsorbed with the active sites on the substrate surface. Due to the self-limiting nature of ALD, only a single atomic layer is formed each time deposition, ensuring the precise thickness and uniform deposition of the material.
[0021] First, the Fe precursor forms a single atomic layer on the surface of the Ni layer through chemical adsorption, and then the unreacted precursor molecules and by-products are removed by inert gas purging to ensure the cleanliness of the film surface, and then the co-reactant is introduced to react chemically with the adsorbed Fe precursor to form a stable metallic Fe layer. The repeatability and accuracy of this process are further ensured by inert gas purging, and impurities can be removed at each step to avoid undesirable reactions in subsequent steps.
[0022] Similarly, the precursors of Co, Ni and rare earth elements are deposited in the same way. Each precursor adsorbs and reacts with its corresponding surface chemical site to form a single atomic layer of metal. The introduction of rare earth elements is particularly important, as it significantly enhances the magnetic anisotropy and mechanical properties of the alloy layer through its special magnetic and crystal properties. During each step of the deposition process, the purge of inert gas removes unreacted substances and by-products to ensure the purity and structural integrity of each metal layer.
[0023] The key mechanism in the entire deposition process is the self-limiting reaction characteristics of ALD. By precisely controlling the adsorption and reaction of metal atoms in each layer, excessive deposition and uneven deposition are avoided, so that the multilayer structure has a high degree of uniformity and precise thickness control. This deposition step is repeated many times, and Fe, Co, Ni and rare earth element atoms are stacked layer by layer, eventually forming a multilayer FeCoNi alloy layer of composite rare earth elements. Since the formation of each single atomic layer is precisely controlled, the entire film structure has excellent magnetic properties, mechanical strength and chemical stability.
[0024] As an optimal technical solution for the preparation of a multilayer iron-cobalt-nickel composite permanent magnetic film, the Fe precursor is FeCl3 or Fe(acac)2, the Co precursor is Co(acac)2, the Ni precursor is Ni(acac)2, and the rare earth element precursor is LaF3.
[0025] It should be noted that in this process, specific metal precursors are selected for the atomic layer deposition (ALD) process, where the Fe precursor is FeCl3 or Fe(acac)2, the Co precursor is Co(acac)2, the Ni precursor is Ni(acac)2, and the rare earth element precursor is LaF3. The selection of these precursors is based on their high volatility, chemical stability, and good reactivity within the deposition temperature range to ensure that they can be precisely deposited in a single atomic layer. When FeCl3 and Fe(acac)2 are used as Fe precursors, they exhibit good reactivity within the deposition temperature range of 150°C to 250°C. FeCl3 can chemically adsorb with the active sites on the substrate surface through chloride groups at high temperatures to form a stable Fe layer. At the same time, Fe(acac)2 has an organic ligand structure, which can release Fe atoms at a lower temperature to ensure the uniformity and high purity of the deposited layer. In the ALD process, the precursor deposits a single layer of Fe atoms through adsorption, reaction, and purging, thereby forming a dense and uniform Fe layer. The Co precursor Co(acac)2 can also react chemically with the active sites on the substrate surface through the acetylacetone ligand within the reaction temperature range. Its deposition mechanism is similar to that of the Fe precursor. It first physically adsorbs on the deposited Fe layer and then reacts chemically with the co-reactant to form a metal Co atomic layer. Since the acetylacetone group is volatile, Co(acac)2 can ensure high-purity Co deposition in the ALD process and combines well with the previous layer of Fe to form a uniform multilayer structure. The Ni precursor (Ni(acac)2) plays a similar role in the ALD process. Ni(acac)2 is a commonly used Ni precursor whose ligand is easily volatile and can achieve good deposition effects at lower temperatures. During the deposition process, Ni(acac)2 reacts with the surface of the Co layer to form a stable Ni layer, ensuring the compactness and uniformity of the metal layer. The deposited Ni layer plays an important role as the basis for further deposition of rare earth elements. The rare earth element precursor LaF3 (lanthanum fluoride) is selected as the source of rare earth elements in the ALD process. As a rare earth fluoride, LaF3 has good decomposition and reaction characteristics at high temperatures. During the deposition process, LaF3 reacts with active sites on the substrate surface to form a single atomic layer of rare earth lanthanum. Since the fluoride structure of LaF3 can effectively inhibit the oxidation effect in the film, the deposited rare earth layer not only improves the magnetic properties of the film, but also enhances the chemical stability and corrosion resistance of the film.
[0026] As a preferred technical solution for the preparation method of a multilayer iron-cobalt-nickel composite permanent magnetic film, the inert gas is N2 or Ar2, and the co-reactant is H2.
[0027] It should be noted that in the atomic layer deposition (ALD) process, inert gases (such as N2 or Ar2) are used to purge unreacted precursors and byproducts to ensure the purity of the deposition environment. H2, as a co-reactant, reduces the metal elements in the precursor to simple substances through a reduction reaction with the metal precursor, and deposits them on the substrate surface to form a high-purity metal or rare earth element atomic layer. This process ensures the uniformity and structural integrity of each layer of film.
[0028] As a preferred technical solution for the preparation method of a multi-layer iron-cobalt-nickel composite permanent magnetic film, in the preparation of the FeCoNi alloy layer, the total thickness of the alloy layer is controlled between 50 nm and 100 nm; the thickness of the rare earth element atomic layer is between 0.5 nm and 1 nm; a Ni layer is deposited on the base material, and the thickness is controlled between 10 nm and 30 nm; a Ni layer is deposited on the FeCoNi alloy layer, and the thickness is controlled between 10 nm and 30 nm.
[0029] It should be noted that in the preparation process, the single layer thickness of the FeCoNi alloy layer is precisely controlled at 0.3 nm to 1 nm, and the total thickness of the alloy layer is 50 nm to 100 nm through multiple depositions, ensuring the uniformity of magnetic properties. The rare earth element layer enhances the magnetic anisotropy, and the Ni layer serves as a bonding and protective layer for the substrate and the alloy layer. Its thickness is 10 nm to 30 nm, ensuring structural stability and optimization of magnetic properties, forming a high-performance multilayer composite film.
[0030] As a preferred technical solution for the preparation of a multilayer iron-cobalt-nickel composite permanent magnetic film, an external magnetic field parallel to the substrate is applied in the deposition chamber during the deposition process, and a parallel magnetic field in the same direction as that during the deposition of the FeCoNi alloy layer is applied during the annealing process.
[0031] It should be noted that applying an external magnetic field parallel to the substrate during the deposition process and applying a parallel magnetic field in the same direction as the FeCoNi alloy layer during the annealing process have a significant optimization effect. First, during the deposition process, the parallel magnetic field can guide the orientation of magnetic atoms (such as Fe, Co, Ni and rare earth elements) so that these atoms are arranged in an orderly manner along the direction of the magnetic field, thereby establishing a consistent magnetic orientation during the film formation process. This orderly arrangement not only enhances the magnetic anisotropy of the film, but also reduces the disordered distribution of the magnetic domain wall, thereby reducing hysteresis loss and improving the overall magnetic properties of the film.
[0032] During the annealing process, continuing to apply a parallel magnetic field in the same direction as during deposition can further strengthen the arrangement of atoms and magnetic domains. The annealing process promotes atomic diffusion and grain reorganization in the film, allowing the magnetic atoms to rearrange more consistently under the guidance of the magnetic field and optimize the magnetic domain structure. At the same time, the magnetic field can promote the preferred orientation growth of grains, further improving the magnetic properties and structural stability of the film. This synergistic magnetic field effect during the deposition and annealing process gives the film higher magnetic anisotropy, coercivity, saturation magnetization and remanence, making it suitable for the application of high-performance magnetic devices.
[0033] As a preferred technical solution for the preparation of a multilayer iron-cobalt-nickel composite permanent magnetic film, magnetron sputtering technology is used in a vacuum environment with a pressure of 10 -3 A Ni layer was deposited under 400 Pa, the deposition temperature was controlled between 250°C and 300°C, and the deposition rate was 1 nm / min.
[0034] It should be noted that in a vacuum environment (pressure 10 -3 Pa), using magnetron sputtering technology to deposit a Ni layer on the substrate at a deposition rate of 1nm / min. The deposition temperature is controlled between 250℃ and 300℃ to ensure that Ni atoms are uniformly deposited on the substrate surface to form a dense Ni film. This process parameter ensures the uniformity, adhesion and good surface quality of the Ni layer by precisely controlling the temperature, pressure and deposition rate, and is suitable for the manufacture of high-precision devices.
[0035] As a preferred technical solution for a method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film, the substrate material is single crystal silicon or aluminum oxide material.
[0036] It should be noted that single crystal silicon or aluminum oxide as substrate materials have excellent chemical stability and mechanical strength, and are suitable for carrying high-quality thin films. During the deposition process, these substrates provide good adhesion and a flat surface for the Ni layer, ensuring the structural stability and uniformity of the film.
[0037] The present invention provides another technical solution. The permanent magnetic thin film material prepared by the above-mentioned preparation method includes an anti-oxidation layer, a main phase layer, a grain boundary diffusion layer and a covering layer. The anti-oxidation layer, the main phase layer, the grain boundary diffusion layer and the covering layer are deposited on a substrate material in sequence. The grain boundary diffusion layer is distributed in the main phase layer. The anti-oxidation layer is a Ni layer, the main phase layer is a FeCoNi alloy layer, the grain boundary diffusion layer is a rare earth element layer, and the covering layer is a Ni layer.
[0038] It should be noted that the permanent magnetic film material prepared by the above-mentioned preparation method includes an anti-oxidation layer, a main phase layer, a grain boundary diffusion layer and a covering layer, and each layer is deposited on the substrate material in sequence to ensure the comprehensive performance of the film. First, the anti-oxidation layer is a Ni layer, which can effectively protect the internal layer structure from oxidation and environmental corrosion and improve the durability of the film. The main phase layer is a FeCoNi alloy layer, which, as the core of the permanent magnetic film, provides strong magnetic properties. The rare earth element layer is distributed in the main phase layer as a grain boundary diffusion layer, which plays a role in inhibiting grain growth and promoting grain boundary stability, thereby optimizing magnetism and improving structural integrity. Finally, the covering layer is a Ni layer, which not only increases mechanical protection, but also further enhances the anti-oxidation performance of the film, ensuring the stability and durability of the overall material in use.
[0039] The method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film of the present invention has a series of significant beneficial effects, especially in the preparation of high-performance magnetic materials. First, by adopting the atomic layer deposition (ALD) technology, iron (Fe), cobalt (Co), nickel (Ni) and rare earth element lanthanum (La) are deposited step by step to achieve a nano-scale multilayer alloy structure. This nanoscale grain structure not only enhances the magnetic properties of the film, but also greatly improves the uniformity and stability of the grains. In traditional thin film materials, uneven grain size often leads to disordered distribution of magnetic domains, thereby causing hysteresis loss and performance degradation. The present invention, by finely controlling the deposition process, makes the grains evenly distributed, and by reasonably controlling the thickness of each layer, ensures the precise structure of the alloy layer. It is this nano-level control that significantly improves the magnetic properties of the film, especially improves the key magnetic indicators such as the magnetic anisotropy, coercive force and saturation magnetization of the material.
[0040] Secondly, the introduction of an external magnetic field during the deposition and annealing process further optimizes the microscopic magnetic domain structure of the film. The external magnetic field can guide the orderly arrangement of magnetic atoms during the deposition process, so that the magnetic atoms tend to be arranged along the direction of the magnetic field in the early stage of film formation, and then establish a consistent magnetic orientation inside the film. The orderliness of this magnetic orientation plays a vital role in improving the magnetic properties of the film. In the traditional deposition process, due to the lack of magnetic field guidance, the magnetic domain orientation is easily arranged in a disordered manner, resulting in increased hysteresis loss, and the magnetic properties of the film are difficult to reach an ideal level. The present invention effectively reduces the disordered movement of the magnetic domain wall through the guiding effect of the external magnetic field, thereby reducing the hysteresis loss. In addition, the continued application of the external magnetic field during the annealing process further promotes the orderly arrangement of atoms and magnetic domains. The high temperature environment during the annealing process is conducive to the diffusion of atoms in the film and the reorganization of grains, and under the guidance of the external magnetic field, these magnetic atoms can be more effectively arranged along the direction of the magnetic field, ensuring that the film has a more consistent magnetic orientation after annealing. Through this magnetic field-assisted process combining deposition and annealing, the thin film material exhibits significantly improved magnetic anisotropy, coercivity, saturation magnetization and remanence.
[0041] The introduction of the rare earth element lanthanum (La) is another important innovation in the present invention. Rare earth elements usually play a significant role in magnetic materials, especially in enhancing magnetism and improving the mechanical properties of materials. The present invention forms a grain boundary diffusion layer by introducing the rare earth element lanthanum between the deposited layers of metal elements such as Fe, Co, and Ni. This diffusion layer not only improves the stability of the grains, but also effectively pins the magnetic domain wall, reduces the movement of the magnetic domain wall, and greatly improves the coercive force of the material. At the same time, the introduction of rare earth elements promotes the formation of a variety of phases, such as Fe3Co2La5, Fe5Ni3La2, etc. These phases further enhance the magnetic properties of the film through lattice distortion and magnetic moment coupling. These new phases not only have a significant effect on improving the saturation magnetization and remanence of the film, but also improve the magnetic anisotropy of the film by optimizing the magnetic domain structure, so that its performance in different magnetic field directions is more consistent. In addition, the introduction of the rare earth element lanthanum can also enhance the chemical stability and corrosion resistance of the material, and extend the service life of the film in harsh environments.
[0042] Through the multilayer structure design of the present invention, the overall performance of the film material has been significantly improved. First, the multilayer structure of metals such as Fe, Co, and Ni ensures the magnetic main phase of the film, providing high magnetism and a stable magnetic domain structure; secondly, the grain boundary diffusion layer of the rare earth element lanthanum inhibits the growth of grains, keeps the grain size at the nanometer level, and improves the magnetic anisotropy and coercive force of the material. Finally, the nickel layer deposited on the surface not only provides good mechanical protection for the film, prevents oxidation and corrosion, but also further improves the overall magnetic properties of the film through its soft magnetism. The introduction of the nickel layer as a covering layer effectively reduces the surface defects of the magnetic domain, making the performance of the film more stable in practical applications.
[0043] In summary, the method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film of the present invention successfully prepares a thin film material with excellent magnetic properties by step-by-step deposition and guidance of an external magnetic field, combined with the grain boundary diffusion effect of the rare earth element lanthanum. The thin film material has high saturation magnetization, high remanence, high coercive force and significant magnetic anisotropy, and can show excellent performance in high-frequency magnetic applications. Through reasonable process design and material selection, the present invention not only has significant advantages in improving the performance of magnetic materials, but also provides important technical support for the development of high-performance magnetic components. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0045] Figure 1 This is an electron microscope image of the alloy layer of the permanent magnetic film prepared in Example 3;
[0046] Figure 2 This is the XRD diagram of the alloy layer of the permanent magnetic film prepared in Example 3. DETAILED DESCRIPTION
[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0049] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0050] Example 1
[0051] A method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film comprises the following technical steps:
[0052] S1. Selecting single crystal silicon as the substrate material;
[0053] S2. Using magnetron sputtering technology, in a vacuum environment, the pressure is 10 -3 A Ni layer was deposited on the substrate material at 250°C and a deposition rate of 1 nm / min. The thickness of the Ni layer was 10 nm. ALD technology was continued to be used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in steps to form a FeCoNi alloy layer of composite La. The thickness of the alloy layer was 100 nm and the thickness of the La atomic layer was 1 nm. Finally, magnetron sputtering technology was used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in a vacuum environment at a pressure of 10 -3 A Ni layer is deposited on the FeCoNi alloy layer under Pa, and the thickness of the Ni layer is 30 nm; during the deposition of the FeCoNi alloy layer, an external magnetic field parallel to the substrate is applied with an intensity controlled at 100 mT;
[0054] Among them, the specific technical steps of using ALD technology to deposit Fe, Co, Ni and La atomic layers step by step on the Ni layer to form a FeCoNi alloy layer composited with La include:
[0055] S21.Fe(acac)2 is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is 150°C. N2 is introduced to purge and remove unreacted Fe(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Fe(acac)2 to form a metallic Fe layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0056] S22. Co(acac)2 is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is 150°C. N2 is introduced to purge the unreacted Co(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Co(acac)2 to form a metallic Co layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0057] S23. Ni(acac)2 is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is 150°C. N2 is introduced to purge the unreacted Ni(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Ni(acac)2 to form a metallic Ni layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0058] S24. LaF3 is adsorbed on the surface of the Ni layer to form a monoatomic layer. The deposition temperature is between 150°C. N2 is introduced to purge to remove unreacted LaF3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed LaF3 to form a La layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0059] S25. Repeat the above steps to gradually form a multilayer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers;
[0060] S3. The deposited film is annealed in an Ar2 atmosphere at a temperature of 500°C for 1 hour. During the annealing process of the FeCoNi alloy layer, an external magnetic field is applied with the same direction as that during the deposition of the FeCoNi alloy layer and with an intensity of 100 mT.
[0061] Example 2
[0062] A method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film comprises the following technical steps:
[0063] S1. Selecting alumina as the substrate material;
[0064] S2. Using magnetron sputtering technology, in a vacuum environment, the pressure is 10 -3 A Ni layer was deposited on the substrate material at 300°C and a deposition rate of 1 nm / min. The thickness of the Ni layer was 30 nm. ALD technology was continued to be used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in steps to form a FeCoNi alloy layer of composite La. The thickness of the alloy layer was 50 nm and the thickness of the La atomic layer was 0.5 nm. Finally, magnetron sputtering technology was used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in a vacuum environment at a pressure of 10 -3 A Ni layer is deposited on the FeCoNi alloy layer under Pa, and the thickness of the Ni layer is 10 nm; during the deposition of the FeCoNi alloy layer, an external magnetic field parallel to the substrate is applied with an intensity controlled at 300 mT;
[0065] Among them, the specific technical steps of using ALD technology to deposit Fe, Co, Ni and La atomic layers step by step on the Ni layer to form a FeCoNi alloy layer composited with La include:
[0066] S21. FeCl3 is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is 250°C. N2 is introduced to purge and remove unreacted FeCl3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed FeCl3 to form a metallic Fe layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0067] S22. Co(acac)2 is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is 250°C. N2 is introduced to purge the unreacted Co(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Co(acac)2 to form a metallic Co layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0068] S23. Ni(acac)2 is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is between 250°C. N2 is introduced to purge to remove unreacted Ni(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Ni(acac)2 to form a metallic Ni layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0069] S24. LaF3 is adsorbed on the surface of the Ni layer to form a monoatomic layer. The deposition temperature is 250°C. N2 is introduced to purge to remove unreacted LaF3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed LaF3 to form a La layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0070] S25. Repeat the above steps to gradually form a multilayer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers;
[0071] S3. The deposited film is annealed in an Ar2 atmosphere at a temperature of 400°C for 1 hour. During the annealing of the FeCoNi alloy layer, an external magnetic field is applied in the same direction as that during the deposition of the FeCoNi alloy layer and with an intensity of 300 mT.
[0072] Example 3
[0073] A method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film comprises the following technical steps:
[0074] S1. Selecting alumina as the substrate material;
[0075] S2. Using magnetron sputtering technology, in a vacuum environment, the pressure is 10 -3A Ni layer was deposited on the substrate material at 280°C and a deposition rate of 1 nm / min. The thickness of the Ni layer was 20 nm. ALD technology was continued to be used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in steps to form a FeCoNi alloy layer of composite La. The thickness of the alloy layer was 80 nm and the thickness of the La atomic layer was 0.5 nm. Finally, magnetron sputtering technology was used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in a vacuum environment at a pressure of 10 -3 A Ni layer is deposited on the FeCoNi alloy layer under Pa, and the thickness of the Ni layer is 10 nm; during the deposition of the FeCoNi alloy layer, an external magnetic field parallel to the substrate is applied with an intensity controlled at 200 mT;
[0076] Among them, the specific technical steps of using ALD technology to deposit Fe, Co, Ni and La atomic layers step by step on the Ni layer to form a FeCoNi alloy layer composited with La include:
[0077] S21. FeCl3 is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is 200°C. N2 is introduced to purge and remove unreacted FeCl3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed FeCl3 to form a metallic Fe layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0078] S22. Co(acac)2 is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is 200°C. N2 is introduced to purge to remove unreacted Co(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Co(acac)2 to form a metallic Co layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0079] S23. Ni(acac)2 is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is between 200°C. N2 is introduced to purge to remove unreacted Ni(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Ni(acac)2 to form a metallic Ni layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0080] S24. LaF3 is adsorbed on the surface of the Ni layer to form a monoatomic layer. The deposition temperature is 200°C. N2 is introduced to purge to remove unreacted LaF3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed LaF3 to form a La layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0081] S25. Repeat the above steps to gradually form a multilayer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers;
[0082] S3. The deposited film is annealed in an Ar2 atmosphere at a temperature of 400°C for 1 hour. During the annealing of the FeCoNi alloy layer, an external magnetic field is applied in the same direction as that during the deposition of the FeCoNi alloy layer and with an intensity controlled at 200 mT.
[0083] Example 4
[0084] A method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film comprises the following technical steps:
[0085] S1. Selecting alumina as the substrate material;
[0086] S2. Using magnetron sputtering technology, in a vacuum environment, the pressure is 10 -3 A Ni layer was deposited on the substrate material at 280°C and a deposition rate of 1 nm / min. The thickness of the Ni layer was 25 nm. ALD technology was continued to be used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in steps to form a FeCoNi alloy layer of composite La. The thickness of the alloy layer was 60 nm and the thickness of the La atomic layer was 0.8 nm. Finally, magnetron sputtering technology was used to deposit Fe, Co, Ni and La atomic layers on the Ni layer in a vacuum environment at a pressure of 10 -3 A Ni layer is deposited on the FeCoNi alloy layer under Pa, and the thickness of the Ni layer is 25 nm; during the deposition of the FeCoNi alloy layer, an external magnetic field parallel to the substrate is applied with an intensity controlled at 250 mT;
[0087] Among them, the specific technical steps of using ALD technology to deposit Fe, Co, Ni and La atomic layers step by step on the Ni layer to form a FeCoNi alloy layer composited with La include:
[0088] S21. FeCl3 is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is 200°C. N2 is introduced to purge and remove unreacted FeCl3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed FeCl3 to form a metallic Fe layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0089] S22. Co(acac)2 is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is 180°C. N2 is introduced to purge the unreacted Co(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Co(acac)2 to form a metallic Co layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0090] S23. Ni(acac)2 is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is between 180°C. N2 is introduced to purge to remove unreacted Ni(acac)2 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed Ni(acac)2 to form a metallic Ni layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0091] S24. LaF3 is adsorbed on the surface of the Ni layer to form a monoatomic layer. The deposition temperature is 180°C. N2 is introduced to purge to remove unreacted LaF3 molecules and by-products. H2 is introduced into the reaction chamber to react with the adsorbed LaF3 to form a La layer. N2 is introduced again to remove unreacted co-reactants and by-products.
[0092] S25. Repeat the above steps to gradually form a multilayer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers;
[0093] S3. The deposited film is annealed in an Ar2 atmosphere at a temperature of 400°C for 1 hour. During the annealing of the FeCoNi alloy layer, an external magnetic field is applied in the same direction as that during the deposition of the FeCoNi alloy layer and with an intensity of 250 mT.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 3 is that in step S2, magnetron sputtering technology is used in a vacuum environment with a pressure of 10 -3 A Ni layer was deposited on the substrate material at 280°C and a deposition rate of 1 nm / min. The thickness of the Ni layer was 20 nm. ALD technology was continued to be used to deposit Fe, Co and Ni on the Ni layer in steps to form a FeCoNi alloy layer. The thickness of the alloy layer was 80.5 nm. Finally, magnetron sputtering technology was used to deposit Fe, Co and Ni on the Ni layer in a vacuum environment at a pressure of 10 -3 A Ni layer is deposited on the FeCoNi alloy layer under Pa, and the thickness of the Ni layer is 10 nm; during the deposition of the FeCoNi alloy layer, an external magnetic field parallel to the substrate with an intensity controlled at 200 mT is applied.
[0096] Comparative Example 2
[0097] The difference between this control example and Example 3 is that the external magnetic field during the deposition process is eliminated.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 3 is that the external magnetic field during the annealing process is eliminated.
[0100] Comparative Example 4
[0101] The difference between this control example and Example 3 is that a total of four layers, namely, Fe atomic layer, Co atomic layer, Ni atomic layer and rare earth element atomic layer, are deposited by ALD technology, instead of cyclic step-by-step deposition as in Example 3.
[0102] The Verslab Vibrating Sample Magnetometer (VSM) produced by Quantum DeSign was used in this experiment. It is an instrument for detecting the magnetism of materials. The temperature range that can be tested is 50-400K, and the maximum external magnetic field is 3 T. The specific test method is: place the sample on the sample stage of the VSM, and record the change in the magnetization intensity of the film by applying a gradually increasing external magnetic field. When the magnetic field gradually increases until the magnetization intensity of the film no longer increases with the increase of the magnetic field, the magnetization intensity reaches the saturation state, and the magnetization intensity at this time is the saturation magnetization intensity (Ms). Subsequently, the external magnetic field is gradually reduced and dropped to zero. During this process, the sample still retains part of the magnetization intensity, which is called remanence (Mr). By drawing a hysteresis loop, the remanence value can be read on the ordinate. When the external magnetic field continues to increase in the opposite direction, until the magnetization intensity is completely offset, the net magnetization intensity of the sample is zero, and the reverse magnetic field intensity at this time is the coercive force (Hc), which represents the ability of the material to resist demagnetization.
[0103] In addition, by rotating the direction of the sample and repeating the above magnetization process at different angles, the changes in magnetization intensity in different directions can be recorded. This angularly resolved magnetic property test can be used to analyze the magnetic anisotropy of the film. In the hysteresis loops in different directions, the saturation magnetization and coercive force of the film will vary with direction. Analysis of these changes can determine whether the magnetization direction of the film has a preferred orientation, thereby evaluating its anisotropic characteristics. Through this comprehensive testing method, the magnetic properties of multilayer iron-cobalt-nickel composite permanent magnetic films can be fully characterized, including saturation magnetization, remanence, coercive force and magnetic anisotropy.
[0104] Table 1 shows the magnetic properties data of Examples 1 to 4 and Comparative Examples 1 to 4
[0105] Group performance Saturation magnetization (Ms) / (emu / g) Remanence (Mr) / (emu / g) Coercivity (Hc) / (Oe) <![CDATA[Magnetic anisotropy (K) / (kJ / m 3 )]]> Example 1 185 85 1201 124 Example 2 179 80 1120 121 Example 3 168 75 958 112 Example 4 192 86 1214 132 Comparative Example 1 82 43 842 46 Comparative Example 2 108 59 845 78 Comparative Example 3 98 54 856 68 Comparative Example 4 102 56 865 69
[0106] Combined with Example 3 and Figure 1 and Figure 2It can be seen that the grain size of the alloy layer of the multilayer iron-cobalt-nickel composite permanent magnetic film prepared by the method of the present application is controlled at the nanometer level and is extremely evenly distributed. This nanoscale grain structure provides an ideal growth environment for the magnetic domains of the material, reduces the disordered movement of the magnetic domain walls, and thus improves the overall magnetic properties of the film. After appropriate annealing treatment, multiple stable phases are formed in the film, such as Fe3Co2La5, Fe5Ni3La2, etc. The generation of these phases not only further enhances the magnetic properties of the material, but also significantly improves the saturation magnetization, remanence and coercive force by optimizing the magnetic domain structure and improving the magnetic anisotropy. This shows that the method of the present application has significant advantages in preparing high-performance multilayer permanent magnetic films.
[0107] It can be seen from Examples 1 to 4 and Table 1 that the saturation magnetization Ms, remanence Mr, coercive force Hc and magnetic anisotropy K of the permanent magnetic film prepared in the present application are 168emu / g to 192emu / g, 75emu / g to 86emu / g, 958Oe to 1214Oe and 112kJ / m 3 Up to 132 kJ / m 3 Through the preparation method of the present application, a multilayer iron-cobalt-nickel composite permanent magnetic film material with excellent magnetic properties was successfully prepared. Its high saturation magnetization, high remanence, high coercivity and significant magnetic anisotropy indicate that the material has great potential in the field of high-performance magnetic applications.
[0108] Combining Example 3, Comparative Example 1 and Table 1, it can be seen that from the comparison of the performance data of Example 1 and Comparative Example 1, it can be seen that Example 1 is significantly better than the performance of Comparative Example 1 in terms of saturation magnetization (185 emu / g), remanence (85 emu / g), coercive force (1201 Oe) and magnetic anisotropy (124 kJ / m3) (saturation magnetization is 82 emu / g, remanence is 43 emu / g, coercive force is 842 Oe, magnetic anisotropy is 46 kJ / m 3 ), which shows that the addition of rare earth elements in Example 1 has significant advantages in improving the magnetic properties of permanent magnetic film materials. It may be that through the addition of La element during the annealing process, new phases such as Fe3Co2La5 and Fe5Ni3La2 are formed, which significantly enhance the magnetic properties of multilayer iron-cobalt-nickel composite permanent magnetic films. These new phases improve the saturation magnetization, remanence, coercive force and magnetic anisotropy of the material through local lattice distortion, magnetic moment coupling and domain wall pinning effect. The assisted deposition of the external magnetic field further promotes the formation and optimization of these new phases, making the material perform well in high-performance magnetic applications.
[0109] Combining Example 3, Comparative Example 2, Comparative Example 3 and Table 1, it can be seen that the saturation magnetization of Example 3 is 168 emu / g, the remanence is 75 emu / g, the coercive force is 958 Oe, and the magnetic anisotropy is 112 kJ / m 3 The saturation magnetization of the comparative example 2 is 108 emu / g, the remanence is 59 emu / g, the coercivity is 845 Oe, and the magnetic anisotropy is 78 kJ / m 3 The saturation magnetization of control example 3 is 98 emu / g, the remanence is 54 emu / g, the coercive force is 856 Oe, and the magnetic anisotropy is 68 kJ / m 3 Obviously, Example 3 is superior to Control Example 2 and Control Example 3 in all magnetic indicators. This may be because during the deposition process, the parallel magnetic field can guide the orientation of magnetic atoms (such as Fe, Co, Ni and rare earth elements), so that these atoms are arranged in an orderly manner along the direction of the magnetic field, thereby establishing a consistent magnetic orientation during the film formation process. This orderly arrangement not only enhances the magnetic anisotropy of the film, but also reduces the disordered distribution of the magnetic domain wall, thereby reducing the hysteresis loss and improving the overall magnetic properties of the film.
[0110] During the annealing process, continuing to apply a parallel magnetic field in the same direction as during deposition can further strengthen the arrangement of atoms and magnetic domains. The annealing process promotes atomic diffusion and grain reorganization in the film, allowing the magnetic atoms to rearrange more consistently under the guidance of the magnetic field and optimize the magnetic domain structure. At the same time, the magnetic field can promote the preferred orientation growth of grains, further improving the magnetic properties and structural stability of the film. This synergistic magnetic field effect during the deposition and annealing process gives the film higher magnetic anisotropy, coercivity, saturation magnetization and remanence, making it suitable for the application of high-performance magnetic devices.
[0111] Combining Example 3, Comparative Example 4 and Table 1, it can be seen that the saturation magnetization of Example 3 is 168 emu / g, the remanence is 75 emu / g, the coercive force is 958 Oe, and the magnetic anisotropy is 112 kJ / m 3 The saturation magnetization of control example 4 is significantly lower, only 98 emu / g, the remanence is 54 emu / g, the coercivity is 856 Oe, and the magnetic anisotropy is 68 kJ / m 3 The magnetic properties of Example 3 are better than those of Control Example 4 in all aspects. The step-by-step deposition process in Example 3 distributes the La element between Fe, Co, and Ni to form a stable grain boundary diffusion layer. This layer plays an important role in optimizing the magnetic domain structure, improving the pinning effect of the magnetic domain wall, and enhancing the grain boundary stability and magnetic anisotropy. Combined with the precise control of the step-by-step deposition and the phase formation during the annealing process, the overall magnetic properties of the film are significantly improved, making it show higher saturation magnetization, remanence, and coercivity.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film, characterized in that: The technical steps include: Select the substrate material; A Ni layer is deposited on the substrate material using magnetron sputtering technology; Fe, Co, Ni and rare earth element atomic layers are deposited on the Ni layer step by step using ALD technology to form a FeCoNi alloy layer of composite rare earth elements; finally, a Ni layer is deposited on the FeCoNi alloy layer using magnetron sputtering technology; The deposited film is annealed in an Ar2 atmosphere at a temperature between 400°C and 500°C for 1 to 2 hours; During the deposition and annealing of the FeCoNi alloy layer, an external magnetic field is applied, and the intensity is controlled between 100 mT and 300 mT; The specific technical steps of using ALD technology to deposit Fe, Co, Ni and rare earth element atomic layers on the Ni layer step by step to form a FeCoNi alloy layer of composite rare earth elements include: The Fe precursor is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Fe precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Fe precursor to form a metal Fe layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts. The Co precursor is adsorbed on the surface of the Fe layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Co precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Co precursor to form a metal Co layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts. The Ni precursor is adsorbed on the surface of the Co layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted Ni precursor molecules and byproducts. A co-reactant is introduced into the reaction chamber to react with the adsorbed Ni precursor to form a metal Ni layer. An inert gas is introduced again to remove unreacted co-reactants and byproducts. The rare earth element precursor is adsorbed on the surface of the Ni layer to form a single atomic layer. The deposition temperature is between 150°C and 250°C. An inert gas is introduced to purge and remove unreacted rare earth element precursor molecules and by-products. A co-reactant is introduced into the reaction chamber to react with the adsorbed rare earth element precursor to form a rare earth layer. An inert gas is introduced again to remove unreacted co-reactants and by-products. Repeat the above steps to gradually form a multi-layer FeCoNi alloy layer of composite rare earth elements by continuously stacking single atomic layers; The Fe precursor is FeCl3 or Fe(acac)2, the Co precursor is Co(acac)2, the Ni precursor is Ni(acac)2, and the rare earth element precursor is LaF3; the inert gas is N2 or Ar2, and the co-reactant is H2.
2. The method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film according to claim 1, characterized in that: In the preparation of the FeCoNi alloy layer, the total thickness of the alloy layer is controlled between 50nm and 100nm; the thickness of the rare earth element atomic layer is between 0.5nm and 1nm; a Ni layer is deposited on the base material, and the thickness is controlled between 10nm and 30nm; a Ni layer is deposited on the FeCoNi alloy layer, and the thickness is controlled between 10nm and 30nm.
3. The method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film according to claim 1, characterized in that: During the deposition process, an external magnetic field parallel to the substrate is applied in the deposition chamber, and during the annealing process, a parallel magnetic field in the same direction as that during the deposition of the FeCoNi alloy layer is applied.
4. The method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film according to claim 1, characterized in that: Using magnetron sputtering technology, in a vacuum environment, the pressure is 10 -3 A Ni layer was deposited under 400 Pa, the deposition temperature was controlled between 250°C and 300°C, and the deposition rate was 1 nm / min.
5. The method for preparing a multilayer iron-cobalt-nickel composite permanent magnetic film according to claim 1, characterized in that: The substrate material is single crystal silicon or aluminum oxide.
6. The permanent magnetic thin film material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The invention comprises an anti-oxidation layer, a main phase layer, a grain boundary diffusion layer and a covering layer, wherein the anti-oxidation layer, the main phase layer, the grain boundary diffusion layer and the covering layer are sequentially deposited on a base material, the grain boundary diffusion layer is distributed in the main phase layer, the anti-oxidation layer is a Ni layer, the main phase layer is a FeCoNi alloy layer, the grain boundary diffusion layer is a rare earth element layer, and the covering layer is a Ni layer.
Citation Information
Patent Citations
Preparation method of metal permanent magnet thin film with multi-layer thin film structure
CN103205787B
Method for in-situ preparationof oxide / metal ferromagnetic heterojunction through atomic layer deposition method
CN105925955A
Method for catalytically synthesizing single-walled carbon nanotubes on basis of atomic layer deposition
WO2023173354A1